PENGARUH UKURAN PERUSAHAAN, FINANCIAL DISTRESS, DAN LEVERAGE TERHADAP INTEGRITAS LAPORAN KEUANGAN - Muhammad Ario W (2020)
This study was conducted to examine the influence of company size, financial distress, and leverage on the integrity of information financial statement. Total population on this research are about 144 companies on manufacture sector that listed on Indonesia Stock Exchange from 2016 until 2018. Sample in this research are selected with purposive sampling method that obtained 122 companie left with 3 observation period. This analysis model used on this research is multiple linier regression and hypothesis testing using classic assumption test, the t-test with a significance level of 5% or 0,05. The results in this study indicates that (1) company size has significance affect on integrity of information financial statement. (2) financial distress has significance affect on integrity of information financial statement. And (3) leverage has significance affect on integrity of information financial statement.